A ocorrência de DTM em indivíduos que se utilizam da montaria diariamente - Silva, Mariana Moreira da (2010)
Introduction: An dysfunction (TMD) is multifactorial, characterized by sings and symptoms, such as strutural factors of the stomatognathic system, psychological and even functional, which has been well researched currently, and controversies. The horse speak today as a therapeutic tool and as research on the subject, this animal may interfere in some way on the rider that can excite facial and postural muscles. Objective: To evaluate the occurrence of TMD in military personnel who use the riding daily to evaluate the correlation between maximum mouth opening without the aid of police officers who have pain and evaluate the classifications of TMD, as distribution of age groups. Methods: We conducted a cross-sectional and observational, with the participation of 40 military officials of the Greater ABC. For the diagnosis and determining the prevalence of TMD questionnaire was used RDC / TMD, Axis I and Axis II, and the evaluators had no communication during the evaluations. Results: To investigate the relationship between groups was performed using the Fisher Exact test considering p <0.05. Among the groups, the higher prevalence of TMD was the police who do not ride the horse. It was also noted that limiting the maximum mouth opening, has no direct relationship with pain, this same group, but the group that mounts the horse, individuals who had no pain had a greater range of mouth opening, compared to individuals with pain, showing that there is a significant statistic difference between mouth opening with and without pain (p = 0.001). And after statistical analysis, the ages were normally distributed for all three types of TMD (Kolmogorov and Smirnov) and the variation of the ages was different among the three groups, according to RDC / TMD (p <0.001). Demonstrating a higher frequency of TMD Group III in the older cops and Group I in the younger officers. Conclusion: The military officers who ride daily in the region of Grande ABC, has a lower prevalence of TMD compared to military officials who do not ride, but the experimental group showed a correlation of maximum mouth opening with pain. It was also possible to conclude that there is a higher incidence of TMD Group III aged between 43 and 50 and Group I in the younger age group (27-34 years).